SWOT Analysis as a Determinant of Marketing Strategy Case - Viviana Viviana; Victor Victor (Almana : Jurnal Manajemen dan Bisnis, 2022)
Technology is increasingly sophisticated so it can provide convenience for mankind. However, it is undeniable that the era of globalization has made transactions easier, but has tightened business competition. This study aims to organize the description by making it controllable. The description is balanced by analysis and delivery into the interpretation. In designing and establishing a marketing strategy, researchers first analyze market segmentation, target market, and market positioning. Then the researchers conducted an environmental analysis consisting of the internal environment and the external environment of PT Karya Lencana Mas Medan. Based on the results of the analysis above, the researchers conducted a SWOT analysis consisting of an analysis of strengths, weaknesses, opportunities, and threats which were then combined in a SWOT matrix, intending to know alternatives which is possible in planning a marketing strategy using a marketing mix analysis consisting of product, price, place, and promotion. Based on the results of the study, it can be concluded as follows. Based on its marketing strategy, PT Karya Lencana Mas Medan is considered quite good, because it has chosen the right segment and is targeted by competitors from the same industry so that the company's market positioning runs smoothly and the marketing mix implemented by PT Karya Lencana Mas Medan is also sufficient. One of the promotions that have been done is canvassing. The current location is also considered strategic because it is in the middle of the city.